ANALYSIS OF VERTICAL MOVEMENTS ON FREEDOM AND BULLET MOVEMENT EVENTS USING VIDEO TRACKING METHOD - Lusia Koja Kanga; Richardo Barry Astro; Yasinta Embu Ika (Program Studi Pendidikan IPA FKIP Universitas Jember, 2021)
Analysis of vertical motion in free fall and bullet motion with the video tracking method has been carried out. This study aims to analyze the vertical motion pattern in the free fall and bullet motion, specifically the ball launching from the edge of the table. The research was carried out by rolling the ball until it slid and releasing the ball from the edge of the table until it experienced a free fall motion with the height of the table from the two activities of about 1 meter. This activity was carried out repeatedly until obtaining 5 videos of each event and recorded using the Vivo android camera. Furthermore, researchers analyzed using the Tracker application to obtain information data about vertical motion patterns, graphs of changes in position with time, and graphs of velocity against time. Result regressive analysis can derive equations Vy = Ax + B and Y = Ax + B